Incentives in HMOs - Martin Gaynor; James B. Rebitzer; Lowell J. Taylor (Levy Economics Institute of Bard College, 2001)
We study the effect of physician incentives in an HMO network. Physician incentives are controversial because they may induce doctors to make treatment decisions that differ from those they would chose in the absence of incentives. We set out a theoretical framework for assessing the degree to which incentive contracts do in fact induce physicians to deviate from a standard guided only by patient interests and professional medical judgement. Our empirical evaluation of the model relies on details of the HMO's incentive contracts and access to the firm's internal expenditure records. We estimate that the HMO's incentive contract provides a typical physician an increase, at the margin, of 0.10 in income for each 1.00 reduction in medical utilization expenditures. The average response is a 5 percent reduction in medical expenditures. We also find suggestive evidence that financial incentives linked to commonly used quality measures may stimulate an improvement in measured quality.
Keywords: 330